The Development of Muhammadiyah Ideology Dar Al-Ahdi Wa Al-Shahadah in Pancasila Course, Law Study Program, Faculty of Law, Universitas Muhammadiyah Sumatera Utara - Abdul Hakim Siagian; Benito Asdhie Kodiyat MS; Andryan Andryan (Randwick International of Social Science Journal, 2021)
Muhammadiyah Business Charitable and the founder of Muhammadiyah Islamic College (MIC), the obligation of an academic community is added to the understanding and practice of Al-Islam Kemuhammadiyahan as a teaching doctrine that follows the Prophet Muhammad SAW, one of the courses that should intersect with Muhammadiyah understanding is the Pancasila course, this course not only describes how the history of Pancasila used as the basis of an independent state, moral value, ethics and diversity that exist, but this Pancasila course should also describe the ideology of Muhammadiyah, the State Law of Pancasila and the ways of practicing it in everyday life of course with Muhammadiyah rules, so that the Pancasila course this is one of the characteristics of the practice of Al-Islam Kemuhammadiyahan in the Legal Studies Program. The research method used in this research is normative juridical.